Improved production of lutein and β-carotene by thermal and light intensity upshifts in the marine microalga Tetraselmis sp. CTP4 - Schüler, Lisa Maylin (2020)
The industrial microalga Tetraselmis sp. CTP4 is a promising candidate for aquaculture feed, novel food, cosmeceutical and nutraceutical due to its balanced biochemical profile. To further upgrade its biomass value, carotenogenesis was investigated by testing four environmental factors, namely temperature, light intensity, salinity and nutrient availability over different growth stages. The most important factor for carotenoid induction in this species is a sufficient supply of nitrates leading to an exponential growth of the cells. Furthermore, high temperatures of over 30 degrees C compared to lower temperatures (10 and 20 degrees C) induced the accumulation of carotenoids in this species. Remarkably, the two different branches of carotenoid synthesis were regulated depending on different light intensities. Contents of beta-carotene were 3-fold higher under low light intensities (33 mu mol m(-2) s(-1)) while lutein contents increased 1.5-fold under higher light intensities (170 and 280 mu mol m(-2) s(-1)). Nevertheless, highest contents of carotenoids (8.48 +/- 0.47 mg g(-1) DW) were found upon a thermal upshift from 20 degrees C to 35 degrees C after only two days at a light intensity of 170 mu mol m(-2) s(-1). Under these conditions, high contents of both lutein and beta-carotene were reached accounting for 3.17 +/- 0.18 and 3.21 +/- 0.18 mg g(-1) DW, respectively. This study indicates that Tetraselmis sp. CTP4 could be a sustainable source of lutein and beta-carotene at locations where a robust, euryhaline, thermotolerant microalgal strain is required.